Pengaruh Penggunaan Model Clil Terhadap Kemampuan Berbicara Mahasiswa Program Studi Pendidikan Bahasa Jerman Universitas Pattimura - Pattinusa, Zusanna; Karuna, Kalvin; Serpara, Henderika (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
Speaking skills as one of the speaking skills has a high frequency of use because it is inevitable in daily activities. The application of content and language integrated learning (CLIL) model in language learning is one way to encourage students to learn language and content (Sprache und Fach) in a balanced manner. This study aims to describe the effect of using CLIL method on students' speaking ability at niveau A2. The research method is an experiment conducted at the German Language Education Study Programme. The research sample was students who attended the A2.1 Productive Sprachfertigkeit course. The data were collected through a speaking test by referring to the A2 test used by the Goethe Institut. Based on the results of data analysis, it is concluded that the application of CLIL method in learning contributes positively to students' speaking ability. This conclusion is based on the results of statistical calculations which show that the calculation value of t= (5.17) is more significant than Ttab (1.82) at the 0.05 level of significance. On the basis of these findings, it is hoped that the CLIL method can be considered as an alternative in learning German, especially to improve speaking skills.